2010
DOI: 10.1155/2010/246845
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Osteocalcin as a Candidate Gene for Type 2 Diabetes (T2D) and Intermediate Traits in Caucasians and African Americans

Abstract: Recent studies in mice and human identified osteocalcin (OCN) as a bone-derived hormone that modulates insulin secretion and insulin sensitivity. OCN is synthesized by the bone gamma-carboxyglutamate protein (BGLAP) gene located in the well replicated region of type 2 diabetes (T2D) linkage on chromosome 1q22. We resequenced BGLAP gene in 192 individuals with T2D and performed case-control studies in 766 Caucasian (461 T2D and 305 controls) and 563 African American individuals (371 T2D and 192 controls). Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…Higher levels of osteocalcin were also associated with a lower odds ratio of developing metabolic syndrome in black and in white nonHispanic individuals [29,38]. A case-control study actually identified coding variants in the fourth exon of human OCN that appeared to correlate with type 2 diabetes in AfricanAmerican patients [39]. However, this finding should be interpreted cautiously as recent genome-wide association studies of large populations, including one specifically performed on an African-American cohort, did not report an association between variants in the human OCN gene and fasting blood glucose or other traits of diabetes [40,41].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…Higher levels of osteocalcin were also associated with a lower odds ratio of developing metabolic syndrome in black and in white nonHispanic individuals [29,38]. A case-control study actually identified coding variants in the fourth exon of human OCN that appeared to correlate with type 2 diabetes in AfricanAmerican patients [39]. However, this finding should be interpreted cautiously as recent genome-wide association studies of large populations, including one specifically performed on an African-American cohort, did not report an association between variants in the human OCN gene and fasting blood glucose or other traits of diabetes [40,41].…”
Section: Clinical Relevance Of the Osteocalcin-mediated Regulation Ofmentioning
confidence: 99%
“…We also used RNA isolated from subcutaneous adipose and skeletal muscle tissue of 168 metabolically characterized subjects (31). Genomic DNA samples from 611 metabolically characterized nondiabetic CA and AA subjects (5) and 718 subjects from 67 CA T2D pedigrees (4,10) were used for sequencing and genotyping studies. Sample characteristics were published elsewhere (4,5,10,31).…”
Section: Human Subjectsmentioning
confidence: 99%
“…Genomic DNA samples from 611 metabolically characterized nondiabetic CA and AA subjects (5) and 718 subjects from 67 CA T2D pedigrees (4,10) were used for sequencing and genotyping studies. Sample characteristics were published elsewhere (4,5,10,31). All study participants provided written, informed consent under protocols approved by the University of Arkansas for Medical Sciences.…”
Section: Human Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al reported an association of variants in BGLAP (Bone γ-carboxy Glutamate Protein gene which synthesizes osteocalcin in humans) with diabetes in African-Americans [45] but that was not replicated in larger well-powered Genome-Wide Association Studies (GWAS) [46]. Most of these studies are observational and cross-sectional in nature and can therefore only show association not causality.…”
Section: Osteocalcin and Glucose Metabolism-evidence In Humansmentioning
confidence: 99%